Human papillomavirus (HPV) vaccine initiation in minority Americans. (March 2017) - De, P.; Budhwani, H.
Abstract: Objectives: Transmission of the human papillomavirus (HPV) is a significant public health concern. HPV is preventable through a series of vaccinations; however, knowledge gaps exist as to which groups are least likely to initiate vaccination. Considering this gap, the aim of this study is to examine HPV vaccine initiation rates in racial minorities, comparing foreign-born individuals to their American-born peers. Study design: Population-based data from the 2013 National Health Interview Survey (NHIS), a repeated large-scale household interview survey of a statistically representative sample of the United States civilian non-institutionalized population, were applied. Data were derived from two survey modules: the family and summary adult modules. Methods: Sampling weights were employed to logistic regression modelling the outcome of HPV vaccine initiation. Results: Foreign-born persons, African Americans, males, those lacking health insurance coverage and those without a medical home (usual place to receive care) held statistically lower rates of HPV vaccine initiation. Being college educated was associated with higher odds of HPV vaccine initiation. Conclusions: Our findings support the persistence of health disparities in racial minorities and foreign-born persons residing in the United States. Addressing these gaps will likely require both individual-level (e.g. targeted health education) and system-level (e.g. HPV vaccine promoting policies) interventions. Since health insurance coverage and having a medical home were significant associates of HPV vaccine initiation, attempts to coverage may improve HPV vaccine initiation rates. Additionally, policies which require HPV vaccination for school entry could boost coverage across all population groups, including boys, foreign-born persons and racial minorities. Highlights: Examines associations between foreign-born status, demographics, health characteristics and HPV vaccine initiation. Analyses nationally representative data from the 2013 National (United States) Health Interview Survey. Those foreign-born, African Americans and males had lower rates of HPV vaccine initiation. Health insurance coverage was positively associated with HPV vaccine initiation. Having a medical home was positively associated with HPV vaccine initiation.